41. Impedance of directional deep bran stimulation leads in subthalamic nucleus: Evaluation of variation in chronic follow up. Issue 12 (December 2017) - Rinaldo, S.; Pilleri, M.; Lettieri, C.; Devigili, G.; Mondani, M.; D'auria, S.; Piacentino, M.; Eleopra, R.
Abstract : The novel Deep Brain Stimulation (DBS) directional leads have a 1.5 mm 2 surface, compared to the 6 mm 2 of standard cylindrical ring leads. The lower contacts surface area physiologically implicates an increment of the impedances values and potential higher fluctuations. The aim of this study is to evaluate the impedances variation overtime in subjects who underwent to DBS surgery with a directional system. Eleven consecutive patients underwent to surgery in bilateral Subthalamic Nucleus (STN) using directional leads. At the activation visit and the subsequent visits, the impedances values were collected up to 12 months. All the patients received the best program set in terms of clinical outcomes. We collect data of more than 160 contacts. A faster impedance increase is detected in early post-operative phase with subsequent decrease over time. 97.5% of therapeutic contacts at 6 months were directional. The fluctuations of the impedances in the active directional contacts appear to be greater than in the cylindrical contacts. The use of a Directional DBS system with constant-current stimulation seems to be a proper tool to maintain the therapeutic stability.